Sistem Informasi Penjualan Pasir Pada PT Tambang Pasir Ranokomea - Hidayat, Haerul; Ningsi, Nurfitria; Paembonan, Solmin (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
This study aims to develop and implement a web-based sales information system at PT Tambang Pasir Ranokomea to enhance the company's operational efficiency and effectiveness. Currently, the company's sales processes are still carried out manually, leading to various issues such as inefficiency in sales data management, limited marketing reach, and the risk of data loss. The information system developed in this study is designed to replace the manual sales processes with a more structured and integrated web-based system. The system development method used is the waterfall model, which includes stages of requirement analysis, system design, implementation, and testing. The system is built using PHP programming language and MySQL database. The system testing was conducted using the Black Box method to ensure the functionality and reliability of the system. The results of the study indicate that this web-based sales information system is capable of addressing the challenges faced by PT Tambang Pasir Ranokomea, simplifying the ordering process for customers, expanding marketing reach, and providing more accurate and real-time sales information. This research makes a significant contribution to the development of web-based sales information systems suitable for the mining industry, particularly in terms of inventory management and logistics. With the implementation of this system, PT Tambang Pasir Ranokomea is expected to improve its operational performance and competitive edge in the market